Impact of Shodhana on the Physico-Chemical Properties and Total Cardiac Glycoside Fractions of the Root Bark of Rakta and Shweta Karavira (Nerium indicum Mill) - Vivek Kumar Patel; Rabinarayan Acharya; Kumari Archana (Wolters Kluwer Medknow Publications, 2024)
Introduction:Rakta and Shveta Karavira, a Upavisha (semi-poisonous), botanically identified as Nerium indicum Mill., is being used in different ayurvedic therapeutics, after proper shodhana (purification) with some specific media. Media such as Godugdha (cow's milk) and Gomutra (cow's urine) have been mentioned in Ayurvedic literature for shodhana of Karavira root bark.Methods:Shodhana of Karavira root barks was carried out using Godugdha (cow's milk), Gomutra (cow's urine), and water media. Standard procedures were followed for performing the physicochemical and phytochemical analysis. To rule out the impact of the shodhana, a high-performance thin-layer chromatography study involved the extraction of total cardiac glycosides (TCGs) fractions.Results:Gross alterations in the drug's appearance, smell, and touch were noticed. Various physicochemical parameters underwent changes. All raw and Shodhita samples contained metabolites such as carbohydrates, alkaloids, glycosides, tannins, and flavonoids. All raw, shodhita, and media had a common value of 0.03 Rf. On spectral comparison, peaks of raw samples coincide with peaks of their respective media samples but none of the shodhita samples.Conclusion:The effect of shodhana on the bark of the Karavira root is confirmed by changes in physicochemical parameters compared to their raw samples. The presence of similar phenotypic molecules, their adsorption behavior, and their spectral characteristics are suggested by samples having a common value of 0.03 Rf. A spectral comparison suggests that TCGs were transferred from the raw samples to the respective media samples.